2022
DOI: 10.1186/s13041-022-00924-9
|View full text |Cite
|
Sign up to set email alerts
|

Antiallodynic effects of KDS2010, a novel MAO-B inhibitor, via ROS-GABA inhibitory transmission in a paclitaxel-induced tactile hypersensitivity model

Abstract: Monoamine oxidase (MAO) inhibitors have been investigated for the treatment of neuropathic pain. Here, we assessed the antiallodynic effects of a novel MAO-B inhibitor, KDS2010, on paclitaxel (PTX)-induced mechanical hypersensitivity. Oral administration of KDS2010 effectively relieved PTX-induced mechanical hypersensitivity in a dose-dependent manner. KDS2010 (25 mg/Kg) significantly prevented and suppressed PTX-induced pain responses with minimal effects on the body weight, motor activity, and working memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Notably, the involvement of oxidative stress has been regarded as an important mechanism in the pathogenesis of neuropathic pain 48,51 . In a line with this, our recent study has shown increased ROS levels contribute to decreased spinal GABA inhibition in a PTX-induced pain hypersensitivity mouse model 46 . KDS, as an MAO-B inhibitor, alleviated pain behaviors by suppressing ROS generation-decreased GABA release, theoretically from spinal astrocytes.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Notably, the involvement of oxidative stress has been regarded as an important mechanism in the pathogenesis of neuropathic pain 48,51 . In a line with this, our recent study has shown increased ROS levels contribute to decreased spinal GABA inhibition in a PTX-induced pain hypersensitivity mouse model 46 . KDS, as an MAO-B inhibitor, alleviated pain behaviors by suppressing ROS generation-decreased GABA release, theoretically from spinal astrocytes.…”
Section: Introductionsupporting
confidence: 63%
“…1B). Based on the previous studies which investigated the pharmacokinetics and toxicokinetics of orally administered KDS 23 , and our primary data on the analgesic effect of KDS on pain models 46 , the dose of 25mg/kg was selected for the treatment due to its effectiveness and limited side effects on the body weight and other essential brain functions (the rats in the KDS-treated group had similar growth in weight, compared to the rats in the SNL-untreated groups). The first round of treatment was conducted from POD3 to POD9.…”
Section: Oral Administration Of Kds Attenuates Mechanical Allodynia F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation- and ROS-associated pathways have been identified as key players in the PTX-induced neuropathic pain. 19,37 Based on the above-mentioned evidence, our study investigated the role of NOX4 in PRMT5-associated PTX-induced neuropathic pain. Moreover, GLX is a reported NOX4 inhibitor by reducing ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of MAO-B decreased hippocampal astrocytic GABA in CIA, rescued cognitive impairment, and alleviated joint swelling in CIA mice ( 183 ). This same group has shown that inhibiting MAO-B has an analgesic effect reversing mechanical allodynia present in neuropathic pain ( 184 ).…”
Section: “Arthritic Brain” and Pain—the Role Of Glia Cellsmentioning
confidence: 99%